Nematode Peptides with Host-Directed Anti-inflammatory Activity Rescue Caenorhabditis elegans from a Burkholderia pseudomallei Infection - Lim, Mei-Perng; Firdaus-Raih, Mohd; Nathan, Sheila (Frontiers in Microbiology, 2016)
Burkholderia pseudomallei, the causative agent of melioidosis, is among a growing number of bacterial pathogens that are increasingly antibiotic resistant. Antimicrobial peptides (AMPs) have been investigated as an alternative approach to treat microbial infections, as generally, there is a lower likelihood that a pathogen will develop resistance to AMPs. In this study, 36 candidate Caenorhabditis elegans genes that encode secreted peptides of <150 amino acids and previously shown to be overexpressed during infection by B. pseudomallei were identified from the expression profile of infected nematodes. RNA interference (RNAi)-based knockdown of 12/34 peptide-encoding genes resulted in enhanced nematode susceptibility to B. pseudomallei without affecting worm fitness. A microdilution test demonstrated that two peptides, NLP-31 and Y43C5A.3, exhibited anti-B. pseudomallei activity in a dose dependent manner on different pathogens. Time kill analysis proposed that these peptides were bacteriostatic against B. pseudomallei at concentrations up to 8× MIC90. The SYTOX green assay demonstrated that NLP-31 and Y43C5A.3 did not disrupt the B. pseudomallei membrane. Instead, gel retardation assays revealed that both peptides were able to bind to DNA and interfere with bacterial viability. In parallel, microscopic examination showed induction of cellular filamentation, a hallmark of DNA synthesis inhibition, of NLP-31 and Y43C5A.3 treated cells. In addition, the peptides also regulated the expression of inflammatory cytokines in B. pseudomallei infected macrophage cells. Collectively, these findings demonstrate the potential of NLP-31 and Y43C5A.3 as anti-B. pseudomallei peptides based on their function as immune modulators.